Challenges of Writing Theses and Dissertations in an EFL Context: Genre and Move Analysis of Abstracts Written by Turkish M.A. and Ph.D. Students - Sükan, Serdar; Mohammadzadeh, Behbood (Frontiers in Psychology, 2022)
Writing a thesis or dissertation is a challenging procedure as it is one of the requirements of getting a graduate and postgraduate diploma. Writing an abstract like other parts of a thesis or dissertation has its criterion. For this reason, due to globalism, those abstracts written by non-native English speakers may lack some of the features of the abstract genre and move that must be included. This study examines the moves of M.A. and Ph.D. abstracts written by Turkish students between the 2009 and 2019 academic years on foreign language education at Cyprus International University. The data consisted of 50 abstracts chosen randomly from the ELT department. For the analysis, Hyland’s five-move model has been used. The study results reveal that 40 abstracts did not follow the five moves that Hyland has put forward. Moreover, it can be stated that the absence of some moves in the abstracts may cause restraint for readers to comprehend these studies in terms of communicative purposes.